Penerapan Model Pembelajaran Discovery Learning terhadap Hasil Belajar Matematika Siswa - Sintia, Sintia; Luthfiana, Maria; Yanto, Yufitri (Jurnal Pendidikan Matematika : Judika Education, 2023)
This study aims to determine the results of learning Mathematics for class VIII students at SMP Negeri 1 Muara Rupit after being given learning using theDiscovery Learning learning model. This study used a quasi-experiment with apopulation of class VIII SMP Negeri 1 Muara Rupit for the 2022/2023 school year and as a sample class, namely class VIIIf, which totaled 25. The data collection technique in this study was a field test. in the form of a description of 8 questions, the results of the study are the average value of students. that is 79,83. Data analysis using the t-test based on the results of the final test with a significant level = 0.05 and the results of the hypothesis test analysis obtained tcount (4,928) > ttable (1.710), so it can be concluded that there is an influence of the Discovery Learning model on mathematics learning outcomes at SMP Negeri 1Muara Rupit in 2022/2023. Keywords: Application, Discovery Learning Model, learningoutcomes